2014
DOI: 10.5194/bgd-11-9889-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are recent changes in sediment manganese sequestration in the euxinic basins of the Baltic Sea linked to the expansion of hypoxia?

Abstract: Abstract. Expanding hypoxia in the Baltic Sea over the past century has led to anoxic and sulfidic (euxinic) deep basins that are only periodically ventilated by inflows of oxygenated waters from the North Sea. In this study, we investigate the consequences of the expanding hypoxia for manganese (Mn) burial in the Baltic Sea using a combination of pore water and sediment analyses of well-dated sediment cores from 8 locations. Diffusive fluxes of dissolved Mn from sediments to overlying waters at oxic and hypox… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 78 publications
(162 reference statements)
2
26
0
Order By: Relevance
“…Ratios of iron over aluminum (Fe/Al) above crustal averages (0.5 wt%/wt%) are typically associated with anoxic and sulfidic basins, where Fe becomes enriched through effective trapping of any incoming Fe from shallower areas (Lyons & Severmann, 2006;Owens et al, 2012). Because input from these shallower areas can be enhanced under anoxic but not sulfidic conditions, Fe/Al can also indicate how widespread anoxia is in a region (e.g., Eckert et al, 2013;Lenz et al, 2015;Raiswell & Anderson, 2005). Molybdenum (Mo) is conservative in oxic waters but is fixed in sediments in the presence of free hydrogen sulfide through conversion of molybdate to particle reactive thiomolybdate (Helz et al, 1996).…”
Section: 1029/2018pa003394mentioning
confidence: 99%
“…Ratios of iron over aluminum (Fe/Al) above crustal averages (0.5 wt%/wt%) are typically associated with anoxic and sulfidic basins, where Fe becomes enriched through effective trapping of any incoming Fe from shallower areas (Lyons & Severmann, 2006;Owens et al, 2012). Because input from these shallower areas can be enhanced under anoxic but not sulfidic conditions, Fe/Al can also indicate how widespread anoxia is in a region (e.g., Eckert et al, 2013;Lenz et al, 2015;Raiswell & Anderson, 2005). Molybdenum (Mo) is conservative in oxic waters but is fixed in sediments in the presence of free hydrogen sulfide through conversion of molybdate to particle reactive thiomolybdate (Helz et al, 1996).…”
Section: 1029/2018pa003394mentioning
confidence: 99%
“…For the Landsort Deep, however, Lepland & Stevens (1998) and Lenz et al (2015a) suggested Mn(Ca)CO 3 formation to occur irrespective of oxygenation events. Lepland & Stevens (1998) related a pronounced Mn (Ca)CO 3 precipitation to the expansion of euxinic bottom waters under increased organic matter input resulting in elevated alkalinity and a Mn surplus due to the reduction of Mn oxides at the basin slope.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Mn oxides accumulate at the sea floor and are converted into Mn(Ca)CO 3 under conditions of increased alkalinity and re-established euxinia. However, recent studies by Lenz et al (2015a) argued that modern oxygenation events may not result in the formation of Mn(Ca)CO 3 layers in the eastern Gotland Basin. High sulphide concentrations in the sediments and in the bottom water following inflow events probably cause the fast dissolution of Mn oxides and the escape of dissolved Mn to the open water column.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations